INVESTIGATION AND STUDY OF THE FINDINGS FROM THE RESCUE EXCAVATION IN SARI GOL CRYPT AND GRAVEYARD, NORTH KHORASAN PROVINCE - Mohsen HEYDARI DASTENAEI; Ebrahim ROUSTAEI FARSI (Journal of Ancient History and Archaeology)
Graveyards are one of the most important archeological sources for studying past humans, which give us information about the material and spiritual cultures of different folks and human groups that lived in the past. One of these graveyards is the Sari Gol Graveyard, located 900 meters southeast of Doulân village in Râz and Jargalân city in the North Khorasan province. This graveyard in the Chandir Dam basin was explored in 2017 to save it. Excavation revealed that there is a two-story Crypt in this cemetery. Its basement part was used as a Crypt, and a room was also on top of the basement. Ten adults and two children were buried in this Crypt, and based on the available evidence, it is clear that these bodies were not buried in the Crypt. However, maybe they were placed on the Crypt floor, and the decomposing of the body was done outside the ground but inside the roofed Crypt. In addition, six graves were also explored around this Crypt, belonging to children and adults. Unfortunately, the skeletons inside these graves have been damaged due to environmental factors such as humidity and plant roots. However, the evidence shows that some people buried in this graveyard have experienced severe physical and work pressures. Also, the evidence from children's graves shows that the children's death is most likely due to an acute illness (such as infectious diseases) among them, a low level of hygiene, and a decrease in their health in this site.